SN 2019hcc: a Type II supernova displaying early O ii lines. Issue 4 (20th July 2021) - Parrag, Eleonora; Inserra, Cosimo; Schulze, Steve; Anderson, Joseph; Chen, Ting-Wan; Leloudas, Giorgios; Galbany, Lluis; Gutiérrez, Claudia P; Hiramatsu, Daichi; Kankare, Erkki; Müller-Bravo, Tomás E; Nicholl, Matt; et al.
ABSTRACT: We present optical spectroscopy together with ultraviolet, optical, and near-infrared photometry of SN 2019hcc, which resides in a host galaxy at redshift 0.044, displaying a sub-solar metallicity. The supernova spectrum near peak epoch shows a 'w' shape at around 4000 Å which is usually associated with O ii lines and is typical of Type I superluminous supernovae. SN 2019hcc post-peak spectra show a well-developed H α P-Cygni profile from 19 d past maximum and its light curve, in terms of its absolute peak luminosity and evolution, resembles that of a fast-declining Hydrogen-rich supernova (SN IIL). The object does not show any unambiguous sign of interaction as there is no evidence of narrow lines in the spectra or undulations in the light curve. Our tardis spectral modelling of the first spectrum shows that carbon, nitrogen, and oxygen (CNO) at 19 000 K reproduce the 'w' shape and suggests that a combination of non-thermally excited CNO and metal lines at 8000 K could reproduce the feature seen at 4000 Å. The Bolometric light-curve modelling reveals that SN 2019hcc could be fit with a magnetar model, showing a relatively strong magnetic field ( B > 3 × 10 14  G), which matches the peak luminosity and rise time without powering up the light curve to superluminous luminosities. The high-energy photons produced by the magnetar would then be responsible for the detected O ii lines. As a consequence, SN 2019hcc shows that a 'w' shape profile at around 4000 Å, usually attributed to O ii, is not only shown in superluminous supernovae and hence it should not be treated as the sole evidence of the belonging to such a supernova type.